Association of infant Rib and Alp1 surface protein N-terminal domain immunoglobulin G and invasive Group B Streptococcal disease in young infants. Issue 10 (3rd March 2023) - Dangor, Ziyaad; Kwatra, Gaurav; Pawlowski, Andrzej; Fisher, Per B.; Izu, Alane; Lala, Sanjay G.; Johansson-Lindbom, Bengt; Madhi, Shabir A.
Highlights: Infant RibN IgG ≥ 0.428 µg/mL was associated with 90 % risk reduction of GBS disease. Infant Alp1N IgG ≥ 0.112 µg/mL was associated with 90 % risk reduction of GBS disease. These protein antibody thresholds are correlates of protection against GBS disease. Such data could contribute to the pathway of licensure of a maternal GBS vaccine. Abstract: Background: Vaccine development for Group B Streptococcus (GBS), a common cause of invasive disease in early-infancy and adverse pregnancy outcomes, include exploring widely-expressed GBS surface proteins as vaccine epitopes. We investigated the association between natural infant serum IgG against the RibN and Alp1N domains and risk of invasive GBS disease caused by isolates expressing these proteins. Methods: We analyzed maternal and infant serum samples from GBS disease cases and infants born to GBS-colonized women controls. Bayesian modelling was used to calculate the GBS homotypic IgG concentration associated with risk reduction of invasive disease in the infant. Results: PCR-based typing of 85 GBS invasive isolates showed 46 and 24 possessing the gene for Rib and Alp1, respectively. These were matched to 46 and 36 infant controls whose mothers were colonized with GBS expressing Rib and Alp1, respectively. RibN IgG geometric mean concentrations (GMC) were lower in cases than controls among infants (0.01; 95 %CI: 0.01–0.02 vs 0.04; 95 %CI: 0.03–0.06; p < 0.001), no significant difference was found between maternal RibN IgG GMC in cases compared to controls. Alp1N IgG GMC was also lower in infant cases (0.02; 95 %CI: 0.01–0.03) than controls (0.05; 95 %CI: 0.04–0.07; p < 0.001); albeit not so in mothers. An infant IgG threshold ≥ 0.428 and ≥ 0.112 µg/mL was associated with 90 % risk reduction of invasive GBS disease due to Rib and Alp1 expressing strains, respectively. Discussion: Lower serum RibN and Alp1N IgG GMC were evident in infants with invasive GBS disease compared with controls born to women colonized with GBS expressing the homotypic protein. These data support the evaluation of Alp family proteins as potential vaccine candidates against invasive GBS disease.